Species diversity and ethnobotanical inventory of wild flora used by the folk community of Shinghar Balochistan, Pakistan - ANWAR UL HAQ; SHAZIA SAEED; Alia Ahmed (Smujo International, 2021)
Abstract. Haq AU, Saeed S, Ahmed A. 2021. Species diversity and ethnobotanical inventory of wild flora used by the folk community of Shinghar Balochistan, Pakistan. Nusantara Bioscience 13: 148-157. Upper Suleiman Mountain of Shinghar Balochistan, Pakistan, is little known by outsiders, and the structural and floristic composition are poorly understood. The dominant socio-linguistic groups of the area are Pashtoon tribes, having a long history of medicinal plants utilization as a part of their indigenous primary health care system. The present study was carried out to describe the plant species diversity of Shinghar and to the inventory of some important wild medicinal, edible and endemic plants of the region. A total of 102 species belonging to 42 families and 88 genera were recorded. Herbs comprised 62% of documented plants, followed by shrubs (26%) and trees (14%). Medicinal plants of the area are being used in the treatment of many ailments like joint pains, stomach problems, skin allergies, and inflammation. Edible plants were 14% of the total recorded plants. The documented plants were also used for other use-categories than medicinal and edible purposes, including fodder, fencing, and ornamental. In addition, some of the medicinal plants were considered poisonous but used for medicine. The area's elevation ranged from 1,700 to 3,400 meters above sea level. The dominating tree was Pinus gerardiana, and the area is also known as the Chilghoza Forest. Asteraceae was the dominating family in the area with 14 species, followed by Lamiaceae (7 species), Poaceae (6 species), Solanaceae, Leguminosae, Fabaceae, and Apocynaceae with 5 species each. The results revealed the importance of the area's endemic and endangered plants that must be conserved. Moreover, the present study highlighted species diversity not earlier described from high altitudes.